2013
DOI: 10.1159/000355099
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotype Distribution in Cytologically Screened Women from Northwest Germany

Abstract: Introduction: In this study, we evaluate the distribution of 24 human papillomavirus (HPV) genotypes in a cohort of 3,381 cytologically screened women from a rural area of northwest Germany, in correlation to cytological diagnoses and histological outcomes. Materials and Methods: We present a retrospective study in which the HPV-genotyping results of women who attended the German cervical screening program were correlated to cytological diagnosis and histological outcome. Results: HPV genotyping showed marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…The association of HPV 73 and HPV82 with cervical epithelial lesions were confirmed and the two types were classified as HR type in previous studies [ 6 ],[ 39 ]. HPV 73 was even more risky than HPV 16 based on HPV-type-specific risk analysis in Bahia, Brazil [ 40 ] and Northwest Germany [ 41 ], which was consistent with our results in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The association of HPV 73 and HPV82 with cervical epithelial lesions were confirmed and the two types were classified as HR type in previous studies [ 6 ],[ 39 ]. HPV 73 was even more risky than HPV 16 based on HPV-type-specific risk analysis in Bahia, Brazil [ 40 ] and Northwest Germany [ 41 ], which was consistent with our results in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of any HPV in SCC samples was 92.2% and was 68.0% across all cervical samples investigated. HR‐HPV was detected in 64.8% of all samples with HPV‐16 being the most common HPV genotype identified, which is consistent with that described elsewhere in CIN cases across Europe in countries such as Spain, France, and Germany [García‐Espinosa et al, ; Monsonego et al, ; de Jonge et al, ; Leinonen et al, ; Rössler et al, ] and in invasive disease internationally [Bosch et al, ; de Sanjose et al, ; Li et al, ]. As previously reported the prevalence of HPV increased through CIN I–III lesions in NI [Anderson et al, ] from 48.1% in CIN I to 81.3% in CIN III cases.…”
Section: Discussionsupporting
confidence: 87%
“…Schiffman et al reported that HPV prevalence was 62%‐17% for ASC‐US, 86%‐56% for LSIL, and 96%‐78% for HSIL cases . HR HPV prevalence in Turkish women with abnormal cytology is similar to rates reported from other countries …”
Section: Discussionsupporting
confidence: 91%
“…In this study, the observed rates of HPV16 (15.7%) and HPV18 (2.9%) infection from cytologically normal samples in our study coincide with those in previous studies . HPV16 and HPV18 were more prevalent in samples with more severe cytological abnormalities ( P < .01).…”
Section: Discussionmentioning
confidence: 99%